Implementasi Algoritma Knuth Moris Pratt Pada Aplikasi Kamus Bahasa Isyarat Berbasis Android - Dwita Deslianti; Chandra Yuliansyah; Deswan Ade Pranata (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2025)
Language is a means of communication. There are various languages in the world, one of them is sign language. Sign language is one of the tools that helps communication between deaf and mutepeople. The communication process between them can be wellunderstood among others because they are used to using the sign language.However, it will be difficult for normal people to understand sign language conveyed by deaf and mute persons because there are differences in communication methods, and vice versa. The problem highlighted in this research is How to implement the KnuthMorisPratt algorithm in sign language dictionary applications so that it can be easily and effectively utilized in teaching Sign language. Theresearch was conducted at the Special Needs School ofDharma Wanita of Bengkulu Province Unity. It was held from March 15, 2019 to April 14, 2019. The data were collected by the Method of Interview, observation, and literature. Based on the results of testing that had been done, the knuthmorrisprat algorithm can be applied in designing sign language dictionary application, so that this application can make easier for users to search for the word to be translated. While the results of blackbox tests thatalso had been done on the application showed that the functions of this application are in line with the expectation. There are no errors or error system in using it.. Keywords—Implementation, Algorithm Knuth Moris Pratt , Language Dictionary